Klub edukasi kesehatan anak “Superman” sebagai upaya mewujudkan Indonesia sehat 2025 - Aditya Zairian; Iskandar Zulkarnain; Muhammad Kurnia Caesar; Yogi Amorega; Fadly Mulia (Unri Conference Series: Community Engagement, 2019)
SDN 120 Pekanbaru is a school located on Jalan Pesisir Ujung RT 3/RW 9 District of Rumbai Pesisir, Kota Pekanbaru, Riau Province. After the survey, this school did not have Usaha Kesehatan Sekolah (UKS) and there were still many students who did not yet have the knowledge and implementation of good health. To solve health problems, the authors provide a solution in the form of a children's health education club called SUPERMAN to be implemented in the school. SUPERMAN is a program with a new concept created to direct elementary school age children to be more concerned with Perilaku Hidup Bersih dan Sehat (PHBS) and the nutrition. The method used in the implementation program is through lectures, training, mentoring, games, and direct applications. The results achieved at this time are the SUPERMAN club has been formed with Semua Sehat; Perbaiki Lemak Dulu; Enaknya di Ruangan; Roar di Outdoor; and Mantap Badanku, Sehat Tubuhku (evidenced by the club's formation certificate, management decree, and club guidebook), members' nutritional status books (there are 6 obese children (21%)), there are five posters and brochures, and the documentation. After this activity was carried out, there wqas an increase in studeny knowledge by 20%.